Oxidomolybdenum complexes for acid catalysis using alcohols as solvents and reactants - Gomes, Ana C.
The application field of dichloridodioxidomolybdenum (VI) chelate complexes, which have been intensively investigated as catalysts for liquid-phase olefin epoxidation, is broadened to encompass acid catalysis, in particular, alcoholysis and acetalisation reactions. Complex [MoO2Cl2(L)] (1) with L = 4,4'-di-tert-butyl-2,2'-bipyridine was chosen as (pre)catalyst. Depending on the reaction conditions, 1 either remained structurally intact or was transformed into different metal species, the structures of which were determined on the basis of single-crystal X-ray diffraction, spectroscopic techniques (FT-IR and H-1 NMR), and elemental analysis. The first example of a mixed-ligand complex of the type [MoO2X(OR)(L)] (X = halide) is disclosed. This complex is one of only a handful of complexes known to date that exhibit an all-cis configuration instead of the usual cis-oxido, trans-X, cis-L configuration (X = anionic ligand). Mechanistic considerations of the formation of the metal species are made.